PEDOMAN PELAKSANAAN SUPERVISI PENDIDIKAN - Nuraini Nuraini (CV. ADIBA AISHA AMIRA, 2025)
Ministry of Education Regulation No. 12 of 2007 concerning Standards for School/Madrasah Supervisors states that every education unit supervisor is required to have six competencies, namely personal competence, managerial and academic supervision competence, educational evaluation competence, research and development competence, and social competence. Two core competencies directly related to supervisory activities in educational institutions are managerial supervision and academic supervision. Managerial supervision aims to improve the quality of school management, while academic supervision focuses on enhancing the quality of teachers' instruction, ultimately leading to improved graduate outcomes. As mentioned earlier, one form of supervision is managerial supervision. This supervision is very important because management is the engine of the organisation that drives all school programmes, starting from leadership, curriculum, student affairs, facilities and infrastructure, budgeting, community relations, and so on. The guidelines for educational supervision in terms of policy can be explained as follows: Law Number 20 of 2003 on the National Education System, Law Number 14 of 2004 on Regional Government, Law Number 5 on Civil Servants, Government Regulation Number 19 of 2005 amended by Number 13 of 2015 and further amended by Number 19 of 2015 on National Education Standards, Government Regulation No. 74 of 2008 on Teachers and Lecturers, Government Regulation No. 17 of 2010 on Discipline of Supervisors, Presidential Regulation No. 14 of 2015 on the Ministry of Education and Culture.